Development of Learning Media for Sports Courses at Cipta Wacana Christian University in the Civil Engineering Study Program - Raditya Pratama; Rafid, Rahmad; Supriadi; Dhayinta, Shellya Tanaya (International Journal of Sustainable English Language, Education, and Science, 2024)
The purpose of this research is to produce a product that will help the teaching and learning process during face-to-face learning conditions. The initial product that will be developed through validation tests by several experts, including material, learning, and media experts. then conducted small group trials and large group trials. After all the stages have been passed, the expected results can help students to understand sports course material during face-to-face sessions. the results of a series of small group trials showed a percentage of 82.2 percent, and the large group obtained a percentage of 86.6 percent.